Aspectos epidemiológicos e clínicos de pacientes com úlcera por pressão internados em uma Instituição Hospitalar, Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2012)
A Pressure Ulcer (PU) is a skin lesion caused by a prolonged tissue ischemia. The aims of this study were: examine the epidemiological and clinical aspects of patients with PU admitted to a hospital in Manaus city; characterize the profile of patients with PU, classify the PU by staging, size, depth, contours / edges, quality and amount of exudate, color, detachment, presence of pain and anatomical location. It was a descriptive transversal study carried out during September-October 2011 in Hospital Units and 28 de Agosto Emergency Hospital. Patients were given by nurses of the unit. Data were collected according to a specific assessment instrument. They were composed of patients characteristics related to sociodemographic and clinical data, ulcer clinical evaluation and anatomic location. The results showed that of 197 patients who were hospitalized in the period of data collection, 53 patients had PU. The prevalence of age was 67.79 years above. The average of time being at the Hospital was two months. It was observed that 74% of patients developed PU in the hospital. The average time for the ulcers formation was one week. Septicemia was the most frequent cause of hospitalization comprising 39.62%. Regarding the anatomical location, sacral region obtained 86.79% of patients with PU. In the classification of PUs Stage II was observed at 32.94% of patients. Most patients had only a percentage of PU with 62.26%. It is the need to promote preventive measures such as implementation of protocols and treatment of Pressure Ulcers in hospital sectors.
Keywords: Enfermagem; Úlcera por pressão; Epidemiologia; Nursing; Pressure Ulcers; Epidemiology; CIÊNCIAS DA SAÚDE